Understanding and preventing cracks in mold steel - Gerson, F. T. (Technical series (Nickel Development Institute (Canada)), 1993)
This publication examines types and causes of cracks in alloy steel molds, the role of mold steel selection in preventing such cracks and a new, inexpensive and disarmingly simple technique which helps to guard against their occurrence.